2004
DOI: 10.2514/1.9278
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Predicted and Measured Formation Flight Interference Effects

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Department of Defense, Washington Headqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…However, this would be a significant piece of work in its own right and is beyond the scope of this paper. For the purposes of this paper, average formation fuel-burn factors per fleet member are estimated using results from [21][22][23][24] for varying fleet sizes as follows: size of fleet n 1 is one, n 2 is 0.9; n 3 is 0.85; n 4 is 0.82; n 5 is 0.8; n 6 is 0.785; n 7 is 0.775. For example, if the front aircraft receives no savings, whereas the follower saves 20%, the resulting average is taken to be 1 0.8∕2 0.9 λ f;n relative to both aircraft in solo flight.…”
Section: Geometric Methods For Finding Optimal Routes For Formatiomentioning
confidence: 99%
See 1 more Smart Citation
“…However, this would be a significant piece of work in its own right and is beyond the scope of this paper. For the purposes of this paper, average formation fuel-burn factors per fleet member are estimated using results from [21][22][23][24] for varying fleet sizes as follows: size of fleet n 1 is one, n 2 is 0.9; n 3 is 0.85; n 4 is 0.82; n 5 is 0.8; n 6 is 0.785; n 7 is 0.775. For example, if the front aircraft receives no savings, whereas the follower saves 20%, the resulting average is taken to be 1 0.8∕2 0.9 λ f;n relative to both aircraft in solo flight.…”
Section: Geometric Methods For Finding Optimal Routes For Formatiomentioning
confidence: 99%
“…Section VI considers the impact on timing and introduces scheduling constraints. Studies based on individual pairings, looking only at the routing problem, have shown potential positive tradeoffs between the diversion to join formation and the reduction in drag formation flight produces [19][20][21][22][23][24]. Formation routes for five aircraft studied by Bower et al [4] focus on aerodynamic aspects such as wing tip separation.…”
Section: Introductionmentioning
confidence: 98%
“…Wind tunnel tests for formation flight have shown that a substantial decrease in drag can be obtained in formation flight depending on the configuration. Blake and Gingras [24] measured a reduction of up to 25% in close formation flight. According to a study of extended formation flight by Ning [1] [26], for streamwise spacings of around 10 to 40 spans with low to moderately low atmospheric turbulence, a two-aircraft formation is capable of achieving a maximum drag reduction of approximately 30%, while a three-aircraft formation showed maximum reductions of around 40%.…”
Section: Savings Versus Safetymentioning
confidence: 99%
“…Since its recognition, various studies have been undertaken to investigate the effects and advantages of formation flight. Some literature studies have focused on close formation flight, illustrated in Figure 2.3, where aircraft are separated by merely a few wingspans [22][23] [24] [25]. Showing good aerodynamic and control benefits, close formation flight minimises the induced drag of an aircraft and should greatly improve fuel efficiency in commercial aviation.…”
Section: Savings Versus Safetymentioning
confidence: 99%
See 1 more Smart Citation